Pengaruh User Generated Content dan Aesthtetic Appeal terhadap Visit Intention pada Jiwan Coffe & Things Cirebon di kalangan Gen Z - Rihke Liestia; Misbak Misbak; Keke Shabrina Nurmalitasari (Journal of Economics and Management Scienties, 2026)
This study aims to analyze the influence of user generated content and aesthetic appeal on Generation Z’s visit intention toward Jiwan Coffee & Things Cirebon. The research employed a quantitative approach with an explanatory research design based on the Stimulus–Organism–Response (SOR) framework. Data were collected through questionnaires distributed to 100 Generation Z respondents in Cirebon Regency who had been exposed to digital content related to Jiwan Coffee. Multiple linear regression analysis was applied using SPSS software. The findings indicate that user generated content has a positive and significant effect on visit intention, while aesthetic appeal does not show a significant partial effect. However, both variables simultaneously have a significant influence on visit intention. The Adjusted R Square value of 0.222 shows that 22.2% of the variation in visit intention can be explained by these variables. These results suggest that authentic user-created content plays an important role in shaping trust, attraction, and imagined visiting experiences among Generation Z. Therefore, strategies to increase visit intention should prioritize optimizing user-generated content while strengthening visual aesthetic quality as a supporting stimulus in digital marketing communication for coffee shop destinations.